Analysis of mannans of two relatively avirulent mutant strains of Candida albicans. - Saxena, A (1989)
We previously reported the isolation of two cerulenin-resistant mutant strains of Candida albicans 4918 that differ in adherence properties and are less virulent than the parental strain. In addition, biochemical characterization demonstrated significant differences in both protein and polysaccharide composition of cell wall material between the mutant and wild-type strains. These observations prompted studies concerning the chemical structure of mannans in these strains. After extraction and subsequent purification by ion-exchange chromatography, mannan fractions were subjected to either mild acid hydrolysis, alkali hydrolysis, or acetylation followed by acetolysis. Acid- and alkali-modified mannans were studied by proton magnetic resonance spectroscopy, and released products were analyzed by high-performance liquid chromatography on an Aminex HPX-42A column. The results demonstrated quantitative and qualitative differences between mannooligosaccharides of the wild-type and mutant strains in the identity of released oligosaccharides as well as in linkage of the oligosaccharides to the protein backbone.